Mgon po Ma niṅ nag poʼi chos skor : a collection of rituals focussing upon Mahakala in the form Mgon-po Ma-nin - Rdo-rje-gliṅ-pa, Gter-ston (Dingo Chentse Rimpoche, 1974)
Teachings of the Nyingmapa tradition of Tibetan Lamaism.